A critical consideration of Hans Kelsen's pure theory of law with particular reference to his concepts of legal norm and basic norm: towards an understanding of the problematic of legal order - Oliver, Gary Alexander (Centre for Law and Society, 2026)
This study aims at distinguishing the subjective and objective aspects of Kelsen's concept.